Forgetting those painful moments. - Waddell, S (2002)
We all know that memories fade-although not always as quickly as we would like. What molecular and cellular processes underlie forgetting? In this issue of Neuron, Schwaerzel et al. indicate that extinction of an odor memory in Drosophila may involve the same neurons as those involved in forming the memory.